The baptism of Jesus in Mark - van Eck, E. (1996)
Jesus' baptism by John the Baptist (Mk 1:9-13) can be understood, from a social- scientific perspective, as a ritual of status transformation. By using insights from social-scientific theories of patronage and clientism, as well as from those of rituals and ceremonies, it is argued that at Jesus' baptism his status is transformed to that of the new broker of the heavenly Patron. Jesus' brokerage in Mark should be seen as the mediating of the Patron's presence and availability to his clients, that is, the proclamation of the kingdom of God, the Patron's new broadened inclusivistic household. After the results of the study are summarised, a few remarks in regard to the possible implications of this study for current historical Jesus research are made.
Keywords: Ritual; Mark 1:9-13; Baptism; Jesus Christ; Theology; Christianity